A New Nonlinear Dynamic Speed Controller for a Differential Drive Mobile Robot - Ibrahim A. Hameed; Luay Hashem Abbud; Jaafar Ahmed Abdulsaheb; Ahmad Taher Azar; Mohanad Mezher; Anwar Ja’afar Mohamad Jawad; Wameedh Riyadh Abdul-Adheem; Ibraheem Kasim Ibraheem; Nashwa Ahmad Kamal (Entropy, 2023)
A disturbance/uncertainty estimation and disturbance rejection technique are proposed in this work and verified on a ground two-wheel differential drive mobile robot (DDMR) in the presence of a mismatched disturbance. The offered scheme is the an improved active disturbance rejection control (IADRC) approach-based enhanced dynamic speed controller. To efficiently eliminate the effect produced by the system uncertainties and external torque disturbance on both wheels, the IADRC is adopted, whereby all the torque disturbances and DDMR parameter uncertainties are conglomerated altogether and considered a generalized disturbance. This generalized disturbance is observed and cancelled by a novel nonlinear sliding mode extended state observer (NSMESO) in real-time. Through numerical simulations, various performance indices are measured, with a reduction of 86% and 97% in the ITAE index for the right and left wheels, respectively. Finally, these indices validate the efficacy of the proposed dynamic speed controller by almost damping the chattering phenomena and supplying a high insusceptibility in the closed-loop system against torque disturbance.